In vivo structure–function analysis of human Dicer reveals directional processing of precursor miRNAs - Gurtan, Allan M. (Cold Spring Harbor Laboratory Press, 2012)
Dicer is an RNase III family endoribonuclease and haploinsufficient tumor suppressor that processes mature miRNAs from the 5′ (5p) or 3′ (3p) arm of hairpin precursors. In murine Dicer knockout fibroblasts, we expressed human Dicer with point mutations in the RNase III, helicase, and PAZ domains and characterized miRNA expression by Northern blot and massively parallel sequencing of small RNAs. We report that inactivation of the RNase IIIA domain results in complete loss of 3p-derived mature miRNAs, but only partial reduction in 5p-derived mature miRNAs. Conversely, inactivation of the RNase IIIB domain by mutation of D1709, a residue mutated in a subset of nonepithelial ovarian cancers, results in complete loss of 5p-derived mature miRNAs, including the tumor-suppressive let-7 family, but only partial reduction in 3p-derived mature miRNAs. Mutation of the PAZ domain results in global reduction of miRNA processing, while mutation of the Walker A motif in the helicase domain of Dicer does not alter miRNA processing. These results provide insight into the biochemical activity of human Dicer in vivo and, furthermore, suggest that mutation of the clinically relevant residue D1709 within the RNase IIIB results in a uniquely miRNA-haploinsufficient state in which the let-7 family of tumor suppressor miRNAs is lost while a complement of 3p-derived miRNAs remains expressed.